Pengaruh Kualitas Fasilitas Pembelajaran terhadap Prestasi Belajar Mahasiswa Program Studi Pendidikan Ekonomi Semester 6 Universitas Bhinneka PGRI Tulungagung Tahun Akademik 2023/2024 - Agustin, Risma Dwi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
High-quality learning facilities can improve student learning achievement, facilitate interaction between lecturers and students, and support the development of practical skills needed in the workplace. Conversely, inadequate facilities can be a barrier in the teaching and learning process, reduce students' enthusiasm for learning, and hinder achieving optimal academic results. This study uses a quantitative approach to identify the extent to which independent variables, such as learning quality and learning facilities, influence learning achievement (dependent variables) both partially and simultaneously at Bhinneka PGRI Tulungagung University. The study population consisted of all 91 students of the 6th Semester Economic Education Study Program, and samples were taken from the entire population using data collection techniques by distributing questionnaires to respondents. The results of partial data analysis indicate that learning quality has a positive and significant effect on learning achievement at Bhinneka PGRI Tulungagung University, with a t-count value (of 2.715) smaller than the t-table (1.987). Learning facilities also positively and significantly affect the learning achievement of Semester 6 students of the Economic Education Study Program with a calculated t-value (5.597) smaller than the t table (1.987). Simultaneously, the quality of learning and learning facilities together have a significant effect on student learning achievement with the F-calculation result (4.026) greater than the F-table (3.10) at a significance level of 0.015 <0.05. The Adjusted R2 value of 0.84 indicates that 84% of the variation in learning achievement is influenced by the quality of learning and learning facilities, while the remaining 16% is influenced by other variables not examined in this study. This study emphasizes the importance of the quality of learning facilities in supporting student academic achievement, as well as providing insight for educational institutions to improve facilities in order to achieve better academic results.